Three new species of Senegalia (Leguminosae-Mimosoideae) from the Atlantic Forest domain, Brazil - Terra, Vanessa; Garcia, Flávia Cristina Pinto (Phytotaxa, 2019)
We describe, illustrate and compare three new Brazilian species of Senegalia from the Atlantic Forest domain: Senegalia atlantica, from Rio de Janeiro State; Senegalia rafinesqueana, from the state of Paraná; and Senegalia cupuliformis, from Bahia State. These species are morphologically most similar to S. tenuifolia and S. multipinnata, S. velutina, and S. kuhlmannii, respectively. Additionally, we provide an identification key to all Senegalia species that are morphologically similar to S. atlantica, S. rafinesqueana and S. cupuliformis and occur in the Atlantic Forest domain; we also provide comments on the geographic distribution and the flowering and fruiting period of S. atlantica, S. rafinesqueana and S. cupuliformis.